2012
DOI: 10.1002/jmv.23453
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of polyomavirus in the saliva of immunocompetent individuals

Abstract: The aim of this study was to investigate and compare the frequency of BKV, JCV, WUV, and KIV in the saliva of healthy individuals. Samples were analyzed for the presence of polyomaviruses (BKV, JCV, WUV, and KIV) DNA by real-time PCR. Of the 291 samples tested, 71 (24.3%) were positive for at least one of the screened polyomaviruses. Specifically, 12.7% (37/291) were positive for WUV, 7.2% (21/291) positive for BKV, 2.4% (7/291) positive for KIV, and 0.3% (1/291) positive for JCV. BKV and WUV co-infections wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 29 publications
2
19
0
2
Order By: Relevance
“…Based on our observation that BKPyV can also infect salivary gland cells in vitro and is associated with pathology in vivo in humans (28, 29, 45, 46), three drugs with demonstrated anti BKPyV activity in kidney cells, CPRO, CDV and LEF were assessed for BKPyV inhibition in salivary gland cells in vitro. It is clear that the kinetics of salivary gland infection are delayed compared to BKPyV infection in kidney cells (Figure 1), thus the response to the agents may vary based on time post infection.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our observation that BKPyV can also infect salivary gland cells in vitro and is associated with pathology in vivo in humans (28, 29, 45, 46), three drugs with demonstrated anti BKPyV activity in kidney cells, CPRO, CDV and LEF were assessed for BKPyV inhibition in salivary gland cells in vitro. It is clear that the kinetics of salivary gland infection are delayed compared to BKPyV infection in kidney cells (Figure 1), thus the response to the agents may vary based on time post infection.…”
Section: Discussionmentioning
confidence: 99%
“…Robaina et al (13) demonstrated that the reactivation of primary infection with polyomaviruses also applies to immunocompetent persons. In saliva samples collected from people aged 15-75 years, about 23.4% were positive for at least one polyomavirus, including 12.7% WU and 2.4% KI.…”
Section: Discussionmentioning
confidence: 99%
“…BKV is generally accepted to latently reside in epithelial cells lining the urogenital tract. However, in immunocompetent individuals, the virus has also been detected in the central nervous system, stool samples, and saliva (19)(20)(21). Since BKV-specific T cells are present in the circulation, one could theorize that they are trafficking to a site of (re)activation.…”
Section: Fig 3 Bkv-specific Cd8mentioning
confidence: 99%